Students’ Creativity in Creating Aromatherapy Candle using Petroleum Learning Design with Radec Model - Wulandari Wulandari; Wawan Wahyu; Wahyu Sopandi (Journal of Educational Sciences, 2020)
The purpose of this study was to observe whether the examined learning design can improve students' creativity. at the petroleum lesson by using the examined learning design. This research was conducted in Madrasah Aliyah Negeri 2 Takengon. The preferred samples were three second-grade students, a chemical teacher, and two expert lecturers. In this study, the method was descriptive. as it involved two experts, who were lecturers, a chemical teacher, and three second-grade high school students. The data collections were carried out through external and internal feasibility tests. An internal feasibility test was conducted on the chemistry teacher and two expert lecturers, while an external feasibility test was conducted on the three second-grade students. Based on the results, the score results in almost every RADEC stage with a percentage of 91.6% and categorized as very strong, except for the sub-indicator of development creativity or enriching ideas acquired scores of 83.3%. These results imply that petroleum oil learning design with the RADEC model is applicable in the learning process to develop students’ creativity. students’ creativity could be improved by applying chemical learning that uses this learning design.